Implementation and adaptation of a statewide recovery friendly workplace initiative toolkit in the United States - Adekemi O. Suleiman; Jennifer E. Sussman; Alversia D. Wade; Nancy Navarretta; Megan A. O’Grady (Public Health in Practice, 2025)
Objectives: Millions consider themselves to be in recovery from a substance use problem. Recovery Friendly Workplaces (RFWs) are an emerging model to engage employers in promoting substance use disorder (SUD) recovery. This paper describes the statewide implementation and adaptation of a RFW Toolkit in Connecticut, United States. The toolkit offers organizations comprehensive guidance on creating supportive work environments for individuals in recovery from SUD. It emphasizes the importance of reducing stigma, enhancing employee well-being, and improving workplace policies related to SUD recovery. Study design: A multimethod statewide evaluation of the RFW Initiative Toolkit. Methods: A focus group, meeting notes and quantitative surveys assessed the RFW toolkit’s use and adaptations in participating organizations across the State as well as policy and practice changes as a result of the RFW process. Summary statistics were calculated for quantitative data and thematic analysis was used for qualitative data. Results: Organizations benefited from toolkit customization and streamlined processes (e.g., templates); practical adaptations increased fit to regional needs and enhanced support systems for employees in recovery. Conclusions: Organizations changed practices, increased training, and created resources as part of the RFW initiative. Future public health practice and evaluation on RFWs should assess organizational readiness to implement new policy and practice related to SUD recovery and adjust implementation and adaptation accordingly. Results provide insights for other states or countries implementing similar workplace initiatives to support SUD recovery.